Measurement Variability Following MRI System Upgrade - Potvin, Olivier; Khademi, April; Chouinard, Isabelle; Farokhian, Farnaz; Dieumegarde, Louis; Leppert, Ilana; Hoge, Rick; Rajah, Maria Natasha; Bellec, Pierre; Duchesne, Simon; , the CIMA-Q group; , the CCNA group (Frontiers in Neurology, 2019)
Major hardware/software changes to MRI platforms, either planned or unplanned, will almost invariably occur in longitudinal studies. Our objective was to assess the resulting variability on relevant imaging measurements in such context, specifically for three Siemens Healthcare Magnetom Trio upgrades to the Prismafit platform. We report data acquired on three healthy volunteers scanned before and after three different platform upgrades. We assessed differences in image signal (contrast-to-noise ratio (CNR)) on T1-weighted images (T1w) and fluid-attenuated inversion recovery images (FLAIR); brain morphometry on T1w image; and small vessel disease (white matter hyperintensities; WMH) on FLAIR image. The results show that for T1w images, the Prismafit upgrade increased the mean and variability of neocortical CNR, while for FLAIR images, no significant difference was observed. Larger volumes of white matter were observed after Prismafit upgrade and a significant relationship was observed between neocortical CNR and cortical volume. WMH were significantly smaller after Prismafit upgrade, when compared to results on the Magnetom Trio. Together, these results indicate that Prismafit upgrade significantly influenced image signal, brain morphometry measures and small vessel diseases measures and that these effects need to be taken into account when analyzing results from any longitudinal study undergoing similar changes.